2022
DOI: 10.1155/2022/7765204
|View full text |Cite
|
Sign up to set email alerts
|

The Descriptive Data Analysis for the Adoption of Community Cloud in Saudi HEI-Based Factor Adoption

Abstract: Due to its increased reliability, adaptability, scalability, availability, and processing capacity, cloud computing is rapidly becoming a popular trend around the world. One of the major issues with cloud computing is making informed decision about adoption of community cloud (CC) computing (ACCC). To date, there are various technology acceptance theories and models to validate perspective of ACCC at both organizational and individual levels. However, no experimental studies have been carried out to provide a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Community cloud which can either be outsourced, hosted inhouse or both, is deployed for group of users, whose common needs or interests make them a community [48]. The commonalities may be nature of work, data utilization, primary services offered or process execution [10].…”
Section: Community Cloudmentioning
confidence: 99%
“…Community cloud which can either be outsourced, hosted inhouse or both, is deployed for group of users, whose common needs or interests make them a community [48]. The commonalities may be nature of work, data utilization, primary services offered or process execution [10].…”
Section: Community Cloudmentioning
confidence: 99%
“…They found that cloud security trust and threats are major issues in a cloud environment. Additionally, Aldahwan and Ramzan (2022) investigate the relationship between various factors and employees' experiences adopting community cloud computing, highlighting security concerns as a significant influencing element. This is similar to Ogunlolu and Rajanen (2019), who mentioned that security is one of the vital factors influencing the adoption of cloud computing.…”
Section: Securitymentioning
confidence: 99%